Pengaruh Biaya Produksi, Operasional, Dan Penjualan Terhadap Laba Bersih Perusahaan Komponen Otomotif BEI 2019-2024 - Frisca Syaharani; Yudiana .; Harun Faizal (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Net income is an important indicator for assessing corporate performance. Automotive and component manufacturing companies face challenges in managing production costs, operating expenses, and sales, making it necessary to examine their effects on net income. This study aims to analyze the effect of production costs, operating expenses, and sales on net income both partially and simultaneously. This study employs a quantitative causal (explanatory) approach. Secondary data were obtained from the annual financial statements of automotive and component manufacturing companies listed on the Indonesia Stock Exchange during 2019–2024. Using purposive sampling, 7 companies with 42 observations were selected. Data were collected through documentation techniques and analyzed using multiple linear regression with SPSS. The findings reveal that production costs have a negative and significant effect on net income (t=-4.378; p<0.001), operating expenses have a positive and significant effect (t=2.439; p=0.020), and sales have a positive and significant effect (t=4.850; p<0.001). Simultaneously, the three variables significantly affect net income (F=195.838; p<0.001) with an Adjusted R Square of 0.934. Efficient production cost management, productive operating expenditures, and increased sales contribute to higher net income. These findings provide practical implications for management in developing cost-control and revenue-enhancement strategies to improve financial performance.